2018
DOI: 10.1055/a-0626-7003
|View full text |Cite
|
Sign up to set email alerts
|

Protective but Non-Synergistic Effects of Nigella Sativa and Vitamin E against Cisplatin-Induced Renal Toxicity and Oxidative Stress in Wistar Rats

Abstract: These results suggest that even though pre-administration of the two agents protect against renal toxicity and oxidative stress, the effects are however not collaborative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
(34 reference statements)
1
6
0
Order By: Relevance
“…Meanwhile treating cisplatinadministrated rats with TQ, Vit E and their combination in G3, G4 and G5, respectively ameliorated the histopathological damage of the renal tissues and nearly restored them to the normal. This result is consistent with that obtained by Busari et al [29]. However, we also found a synergistic effect of TQ and Vit E in ameliorating cisplatin induced nephropathy.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Meanwhile treating cisplatinadministrated rats with TQ, Vit E and their combination in G3, G4 and G5, respectively ameliorated the histopathological damage of the renal tissues and nearly restored them to the normal. This result is consistent with that obtained by Busari et al [29]. However, we also found a synergistic effect of TQ and Vit E in ameliorating cisplatin induced nephropathy.…”
Section: Discussionsupporting
confidence: 94%
“…However, we also found a synergistic effect of TQ and Vit E in ameliorating cisplatin induced nephropathy. This may be due to direct application of thymoquinone instead of nigella sativa that was previously used [29].…”
Section: Discussionmentioning
confidence: 99%
“…Protective effect against cisplatin-induced renal toxicity and oxidative stress in wistar rats 100-200 mg/kg of body weight for 5 days [118] Ocimum basilicum L.…”
Section: Ethanol Extract Ratsmentioning
confidence: 99%
“…In their study, they showed that the combination of NS and Vit E, despite their antioxidant effects, did not show significant additive effects. 16 On the contrary, the observed result of the combination was less than the effect observed with each agent individually. NS may act differently and be pro-oxidant rather than an antioxidant in particular cells or organs.…”
Section: Discussionmentioning
confidence: 93%